2002
DOI: 10.1002/bit.10192
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the adhesion of motile and nonmotile Escherichia coli to a glass surface using a parallel‐plate flow chamber

Abstract: A parallel-plate flow chamber was used to measure the attachment and detachment rates of Escherichia coli to a glass surface at various fluid velocities. The effect of flagella on adhesion was investigated by performing experiments with several E. coli strains: AW405 (motile); HCB136 (nonmotile mutant with paralyzed flagella); and HCB137 (nonmotile mutant without flagella). We compared the total attachment rates and the fraction of bacteria retained on the surface to determine how the presence and movement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 39 publications
6
76
0
Order By: Relevance
“…It has been suggested that swimming motility allows improved access to surfaces for initial attachment (22,35). In low-shear environments, however, motility has been shown to have no effect on attachment of E. coli to glass (36). It has long been known that E. coli can adhere to surfaces via flagella (37), and somewhat more recently, several pathogenic strains have been shown to adhere to epithelial tissue using flagella-mediated adhesion (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that swimming motility allows improved access to surfaces for initial attachment (22,35). In low-shear environments, however, motility has been shown to have no effect on attachment of E. coli to glass (36). It has long been known that E. coli can adhere to surfaces via flagella (37), and somewhat more recently, several pathogenic strains have been shown to adhere to epithelial tissue using flagella-mediated adhesion (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…However, the model does not account for the fact that a higher flow rate promotes higher shear stresses that may prevent cellular attachment [42]. This hindrance may be overcome by the bacterial appendages used in adhesion [43]. Moreover, since these structures have a small size, they can help to overcome the energy barrier between the bacteria and the surface and facilitate adhesion [44].…”
Section: Discussionmentioning
confidence: 99%
“…It is however plausible that this effect is dependent on the bacteria and surface that is used for the assays. When PDMS is used as substrate, since this surface is thermodynamically more favorable for adhesion, the inhibitory effect caused by the shear stress is only noticed after 13 min possibly due to the reduction of free area available for adhesion and the lower contact time between the cells and the surface, which may hamper the adhesion assistance effect provided by the cellular appendages [43].…”
Section: Discussionmentioning
confidence: 99%
“…Motility itself is thought to enhance the initial interaction of the bacterium with the surface by enabling the bacterium to overcome long-range repulsive forces, thus increasing the likelihood of close approach (86). In fact, flagellar motility has been demonstrated to accelerate surface adhesion for many bacteria (169,173,192,217,224,325,344). However, under certain growth conditions, mutation of components of the flagellar structure leads to increased synthesis of the adhesive matrix that promotes interbacterial attachments and formation of a multilayer biofilm.…”
Section: Types Of Adhesive Structures Used To Form the Monolayer Biofilmmentioning
confidence: 99%